Від етнічного до транснаціонального: українська канадська література в пошуках дому - Шадріна, Тетяна Володимирівна; Shadrina, T. V. (Миколаїв : Вид-во ЧНУ ім. П. Могили, 2019)
Досліджується специфіка формування національної ідентичності у різних генерацій канадців українського походження та особливості репрезентації множинної ідентичності в художньому просторі творів українських канадських авторів. Моделі ідентичностей, які описують українські канадські автори, мають ознаки перехідності, зміни, помежів’я. Визначальним для подолання кризи особистісної ідентичності для митців слова є питання переосмислення психічної локації дому. Дім є основоположним фактором формування / (ре)конструкції національної ідентичності для громади, яка відщепилася від своєї нації, і намагається вкоренитися в чужому соціокультурному просторі. Дім виступає символом приналежності, вкоріненості народу, своєрідним маркером набуття / втрати батьківщини. Невизначеність психічної локації дому українських канадських авторів спричинює розмивання ідентичності та, як наслідок, призводить до перманентного коливання поміж двох культур. The article researches the specificity of the formation of national identity in different generations of Canadians of Ukrainian origin and peculiarities of the representation of plural identity in the artistic space of works by Ukrainian Canadian authors. Identity models, which are described by Ukrainian Canadian authors, have signs of transience, change, and borderless. The purpose of the investigation is to find out the specifics of the formation of a national identity (in its relations with other modes) in different generations of Canadians of Ukrainian origin and the peculiarities of the expression of multiple identities in the artistic space of the works by Ukrainian Canadian authors; study of the presented problems of the crisis of personal identity in the English-speaking Ukrainian Canadian literature and the ways to overcome it by the authors. The key to overcoming the crisis of personal identity for word artists is the question of redefining the mental location of the house. Home is a fundamental factor in the formation / (re)construction of a national identity for a community that has been detached from its nation and tries to take root in another‟s socio-cultural space. The home serves as a symbol of belonging, the rooting of the people, a peculiar marker of the acquisition / loss of the homeland. The uncertainty of the mental location of the home of Ukrainian Canadian authors causes identity erosion and, as a result, leads to permanent fluctuations between two cultures.
From ethnic to transnational: ukrainian canadian literature in search of a home
Keywords: національна ідентичність; українські канадські автори; покоління; дім; подвійна ідентичність; national identity; Ukrainian Canadian authors; generation; home; dual identity